Tahlil Maharah al-Istima’ fi Kitab Durus al-Lughah al-‘Arabiyyah li al-Fashl al-Awwal fi al-Madrasah al-Ibtidaiyyah bi Wizarah al-Syu’un al-Diniyyah li Manhaj 2013 - Nasuha, Ali; Sepputri, Elsa (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2023)
This research is motivated by the discrepancy between the composition of Itima' material in the Arabic Language Book Class 1 Madrasah Ibtidaiyah and the standard of presentation of istima' material by Abdurrahman bin Ibrahim al-Fauzan. Therefore, this study aims to see the suitability of the preparation of the book material in the Arabic Language Book of Class 1 Madrasah Ibtidaiyah with the standard presentation of the book material by Abdurrahman bin Ibrahim al-Fauzan. This research method uses a library research approach. The data sources used in this research are books, journals, and internet sites related to the chosen topic. Data collection techniques by identifying discourse from books, articles, journals, internet and other related information. Furthermore, it is analyzed by descriptive analysis method, namely by collecting and compiling a data, then analyzing the data. From the results of the analysis of the Istima' material in the Arabic Language Book for Class 1 of Madrasah Ibtidaiyah, it was found that the Istima' material in the Arabic book was in accordance with the standard for presenting the book's material, but still needed improvements in certain parts. This is evidenced by the use of special material in the Arabic language book in the Arabic language learning process, and the content of the existing material is in accordance with the level of student needs.